Characterization of the Lagerstroemia suprareticulata chloroplast genome and comparative analysis of the crape myrtle (Bangladesh Journal of Botany, 2025)
Lagerstroemia suprareticulata, a critically endangered species indigenous to the southwestern region of Guangxi, China, holds considerable potential for various applications. Yet, its genetic blueprint remains largely uncharted. We sequenced, assembled, and dissected the chloroplast genome (CPDNA) of L. suprareticulata to delineate its genomic architecture, evolutionary divergence, and its phylogenetic stance within the Lagerstroemia genus. This CPDNA spans 152,196 bp with a circular quadripartite structure: 84,027 bp large single-copy (LSC), 16,919 bp single-copy (SSC) region, and two 25,625 bp inverted repeat (IR) regions. Notably, genomic structure, gene content, repeats, IR dynamics, and sequence divergence among five related lythraceous species are largely conserved with slight variations. Six intergenic regions and one protein-coding gene exhibit high diversity, useful as molecular markers for phylogeny and species differentiation.. Phylogenetic assessments employing full CPDNA and coding sequences elucidate that         L. suprareticulata aligns as the progenitor of L. glabra and L. anhuiensis. This analysis offers a thorough perspective on the CPDNA of L. suprareticulata, thus augmenting the genomic resources available for probing its evolutionary lineage and genetic diversity.Bangladesh J. Bot. 54(3): 677-685, 2025 (September) Special